Perbandingan Psikoanalisis Novel Sunyi Adalah Minuman Keras dengan Novel Convenience Store Woman - Tiara Tri Dewi; Syahrul Ramadhan; Tressyalina Tressyalina; Afnita Afnita (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This paper examines the comparison between two literary works in the form of novels originating from Indonesia and Japan. The novels under study are